2006
DOI: 10.1021/ja065638a
|View full text |Cite
|
Sign up to set email alerts
|

AlMe3and ZnMe2Adducts of a Titanium Imido Methyl Cation:  A Combined Crystallographic, Spectroscopic, and DFT Study

Abstract: A combined experimental and DFT study of the reactions of the titanium imido methyl cation [Ti(NtBu)(Me3[9]aneN3)Me]+ (4+) with AlMe3 and ZnMe2 is described. Reaction of 4+ with AlMe3 gave [Ti(NtBu)(Me3[9]aneN3)(mu-Me)2AlMe2]+ (7+), the first structurally characterized AlMe3 adduct of a transition metal alkyl cation and a model for the presumed resting state in MAO-activated olefin polymerizations. Reaction of 4+ with ZnMe2 also gave a methyl-bridged heterobinuclear species, namely [Ti(mu-NtBu)(Me3[9]aneN3)(mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 85 publications
3
58
0
1
Order By: Relevance
“…[34][35][36] In this context the first AlMe3 adduct of a TM-alkyl cation, a heterobimetallic species containing a titanium imido methyl cation, has been structurally characterized by Mountford et al This species is a model for the proposed resting state during MAO activated catalytic olefin polymerization (Scheme 5). 37 A unique structurally characterized AlMe3 adduct of an ansa-zirconoceneMe cation has been also reported. 38 Recent examples of nonmetallocene catalysts for ethylene polymerization are the neutral methyl complexes of titanium stabilized with bulky iminato ligands (L)TiMe2X (L = imidazolin-2-imide; X = Cl or Me).…”
Section: General Methods For the Generation Of Tm-ch3 Bonds In Transimentioning
confidence: 96%
“…[34][35][36] In this context the first AlMe3 adduct of a TM-alkyl cation, a heterobimetallic species containing a titanium imido methyl cation, has been structurally characterized by Mountford et al This species is a model for the proposed resting state during MAO activated catalytic olefin polymerization (Scheme 5). 37 A unique structurally characterized AlMe3 adduct of an ansa-zirconoceneMe cation has been also reported. 38 Recent examples of nonmetallocene catalysts for ethylene polymerization are the neutral methyl complexes of titanium stabilized with bulky iminato ligands (L)TiMe2X (L = imidazolin-2-imide; X = Cl or Me).…”
Section: General Methods For the Generation Of Tm-ch3 Bonds In Transimentioning
confidence: 96%
“…Finally, we will calculate the rate constant for these reactions using conventional transition state theory (TST). In recent years, DFT [13][14][15][16][31][32][33][34] has attracted considerable attention and has been widely applied to electronic structure calculations for systems containing transition metals. DFT methods have been shown to be particularly useful and computationally efficient for systems with a relatively large number of electrons.…”
Section: Resultsmentioning
confidence: 99%
“…However, this was not structurally characterised [121]. In 2006, Mountford et al [122] reported the first cationic transition metal compound containing a M(l-Me 2 )AlMe 2 moiety characterised by X-ray crystallography (20, Fig. 8).…”
Section: Alme 3 and Its Effects On Alkyl Cations And Polymerisationmentioning
confidence: 99%
“…Indeed in some cases, it has been shown that a molecule of solvent would rather bind to the vacant site of the cation than [BF 20 ] -; this is a testament to the anion's non-coordinating nature [133][134][135] -can interact with cations sufficiently to form higher aggregates [137]. Marks et al [138] reported using similar PGSE NMR measurements in C 6 [121,122] quadruples or even hextuples in solution at higher concentrations. It is worth noting that the previously mentioned PGSE NMR experiments were carried out at concentrations above that which is usually used in single-site catalysis, and the existence of these aggregates at lower, more relevant, concentrations is more unlikely.…”
Section: Anion and Solvent Interactionsmentioning
confidence: 99%